OCCURRENCE OF Dictyocaulus filaria INFECTION IN AN ORGANIZED SHEEP FARM OF TAMIL NADU, INDIA - M. Prabhu; C. Sreekumar; N. Prema; P.C. Sakthivel; R. Anilkumar; M. Iyue (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The sheep lungworm Dictyocaulus filaria is of world-wide distribution and causes verminous pneumonia which may result in weight loss and death of the infected sheep. The current investigation was carried out in an organized farm in the Nilgiris district of Tamil Nadu, India during the period from 2012 to 2014. Infected sheep showed clinical illness varying from dullness, depression, moderate coughing, dyspnoea and labored breathing with little mortality. On necropsy, both larval and adult stages of lungworm were recovered from trachea, bronchi and bronchioles. The identity of the nematodes was confirmed as D. filaria based on the socks shaped spicules in males and anterior knob in the larva. Of the 55 animals, including 17 lambs examined during the study period, eight animals were confirmed to have died due to verminous pneumonia. Apart from that, in a few lambs, lung abscess was noticed. Though the infection was present throughout the year, the clinical illness was pronounced in dry summer (n=23) and rainy season of south west monsoon (n=19). The disease was managed by minimizing the exposure of lambs to the contaminated pasture and by deworming with two doses of levamisole hydrochloride @ 7.5 mg/ kg body weight at 21 day interval to control the lungworm infection in sheep.